Russia among the Countries of the Baltic Region - Fedorov, Gennady M.; Korneevets, Valentin S.; Tarasov, Ilya N.; Chasovskiy, Vladimir I. (International Journal of Economics and Financial Issues, 2016)
The Baltic region incorporates interactions of eight EU countries and the Russian Federation. It is composed of Sweden, Denmark, Finland, Lithuania, Latvia, and Estonia, as well as the territories of Russia, Germany and Poland located on the Baltic coast. Subjects of the Russian Federation located in the Baltic region account for 16% of the territory, 20% of the population, and 15.5% of GDP. An even bigger role is of Russia at the national level among the countries of the Baltic region. It accounts for 91% of the territory, 50% of the population, 38% of GDP and 14% of foreign trade turnover of nine countries combined. New spatial forms of cooperation are being formed with Russian participation – Euroregions, cross-border clusters. International cooperation increases the global competitiveness of each of the participating countries. The development gap has decreased between more and less wealthy countries. However, in the past few years, the relationship between the EU and Russia has deteriorated. In 2014 – 2015 Russia's trade with the countries of the region decreased more than with other EU countries and the world. The mutual and social ties decreased. This is not conducive to socio-economic development of both Russia and the EU, and it is in the interest of both parties to abandon the growing confrontation. Keywords: international regionalization, Baltic region, Baltic countries, EU, Russia JEL Classifications: F15, F36, F42, F55